Rabiomas: Aplicativo Androide destinado ao estudo dos biomas brasileiros - Marques, Raimunda Aline Djanira Freire (2019)
Information and Communication Technologies (TICs) have been constantly used as auxiliary tools of the teaching and learning process. By making the classes more dynamic and, consequently, attracting attention and arousing the students' interest, their use has become common in educational institutions. In this research we cover a special type of TIC, Augmented Reality (AR), a technology that enables the overlap and alignment of real and virtual objects in a real-time and real environment. By this way, we will encourage the use of students’ smartphones for educational purposes, since their handling is constant during classes for entertainment. Thus, the main question that guides this study is: "How can an application with RA technology contribute to learning about Brazilian Biomes?". To answer this question, high school students (MS) developed, under the supervision of this researcher, an application with RA, the RAbiomas. The application was validated by a semi-structured questionnaire with the objective of investigating the perception of teachers in the disciplines of Biology and Geography, as well as students of the 3rd year of High School regarding the developed application. Some errors, such as bugs, were presented by the participants and later corrected by the development team. After the validation of the app, we analyzed the use of the app as a potentially significant tool for learning Brazilian Biomes content, in 3rd year classes of the MS, in a vocational school located in Caucaia / Ce. For this validation we used a semi-structured questionnaire with the objective of investigating the perception of teachers of the subjects of Biology and Geography, as well as students of the 3rd year of the MS regarding the developed application. After this stage some modifications were made for its later application as a pedagogical tool. We approached the content related to the World Biomes and the analyzed classes were divided into two groups, one attended a theoretical class about Brazilian Biomes and the other group just made use of the app. As a form of assessment, we applied the pre-test questionnaire to check students' previous knowledge about the subject and post-test to analyze if there was learning after using the application. The observed results showed that the RAbiomas app is a potentially significant tool, helping to stimulate interest and provide student learning.